Реставрація поверхонь шипів хрестовин карданних валів автомобілів за допомогою електроіскрового нарощування - Богатчук, І. М.; Прунько, І. Б. (НТУ "ХПІ", 2015)
Обґрунтовано доцільність використання електроіскрового нарощування для відновлення розмірних параметрів і експлуатаційних властивостей шипів хрестовин карданних валів. Розроблено оправку для мікроскопічних досліджень шару, отриманого методом електроіскрового нарощування на циліндричну поверхню. Проведено замірювання твердості отриманого шару і зроблено висновки щодо експлуатаційних властивостей реставрованої поверхні. Запропоновано спосіб відновлення і зміцнення зношених робочих поверхонь шипів хрестовин карданних валів, придатний для застосування в умовах авторемонтних майстерень підприємств нафтогазового технологічного транспорту.

The expediency of using electro-building to restore dimensional parameters and performance properties of thorns frogs driveshafts. Developed mandrel microscopic studies layer obtained by electro-capacity cylindrical surface. A measurement of the hardness of the resulting layer and draw conclusions on the performance properties of the restored surface. Since the electric-heat treatment does not cause significant amounts of basic metal parts, so there are no deformities and changes in the structure of the base metal. The presence of micropores on the outer surface of the machined parts contributes to the maintenance of oil, and therefore improves the tribological properties of the surface. Based on the research structure of extension layers obtained using different modes of electric-treatment, found that by using electrodes T15K6 and BK8 maximum thickness of the layers was 300 mm, the microhardness of about 10 GPa, obtain their energy by a single pulse of 0.42 and 0, 75 J. tool vibration and frequency of 250 ± 50 and 125 ± 25 Hz, respectively. These modes of treatment is most suitable for restoring worn out surfaces thorns frogs driveshafts. Together with the ease of processing used for electric equipment, this method of restoration can be recommended for use in workshops.
Restoration surfaces thorns frogs cardan shafts using electro-building
Keywords: обробка; відновлення; експлуатаційні властивості; ремонт; crosses; propeller shaft; processing-tension building; restoration